Applications of Generalized Weighted Statistical Convergence to Approximation Theorems for Functions of One and Two Variables. (27th December 2020) - Özger, Faruk
Abstract: In this article, we apply weighted A − statistical convergence to obtain some general approximation results for λ − Bernstein operators. We prove a weighted A − statistical Voronovskaja-type approximation theorem. We support our theoretical parts about approximation properties of constructed bivariate λ − Bernstein operators with numerical results and graphics.